2014
DOI: 10.1002/etc.2563
|View full text |Cite
|
Sign up to set email alerts
|

The importance of experimental time when assessing the effect of temperature on toxicity in poikilotherms

Abstract: Article (refereed) -postprintNorhave, Nils J.; Spurgeon, David; Svendsen, Claus; Cedergreen, Nina. 2014. The importance of experimental time when assessing the effect of temperature on toxicity in poikilotherms. Environmental Toxicology and Chemistry, 33 (6). 1363-1371. 10.1002/etc.2563 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Reproduction, final body length, lifespan and PGR could be described with concentration-response curves for all studies under the different temperature regimes ( Table 3 ). Consistent with our hypothesis, increasing temperature to constant 24°C resulted in a lower EC 50 for all responsive traits than at 12, 16 and 20°C, consistent with previous work and expectations [ 22 ]. The largest shift in sensitivity was seen for PGR for which the EC 50 reduced from 61.2 mg Cu L -1 at 12°C to 25.5 mg Cu L -1 at 20°C.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Reproduction, final body length, lifespan and PGR could be described with concentration-response curves for all studies under the different temperature regimes ( Table 3 ). Consistent with our hypothesis, increasing temperature to constant 24°C resulted in a lower EC 50 for all responsive traits than at 12, 16 and 20°C, consistent with previous work and expectations [ 22 ]. The largest shift in sensitivity was seen for PGR for which the EC 50 reduced from 61.2 mg Cu L -1 at 12°C to 25.5 mg Cu L -1 at 20°C.…”
Section: Resultssupporting
confidence: 93%
“…elegans to Cu-stress at the different constant temperatures partly confirmed the study of Nørhave et al [ 22 ], who found a 1.5 to 2.5-fold decrease in Cu EC 50 increasing temperatures from 11 to 24°C, and in addition found stimulations of reproduction and PGA at low Cu concentrations indicative of hormesis. However, going beyond Norhave et al [ 22 ], the inclusion of a lower temperature treatment at 8°C (as compared to the lowest temperature treatment of 11°C used by [ 22 ]) showed an increase in sensitivity to Cu at low temperature, based on the EC 50 values for the different endpoints ( Table 3 ). Hence, an innately stressful temperature regime was shown to increase the sensitivity of C .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations